PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP KEMAMPUAN MOTORIK KASAR PADA ANAK TK KELOMPOK B2 USIA 5-6 TAHUN DI TK AL-BIRUNI MANDIRI JIPANG - Fadillah Putri Nadia; Ismail Tolla; Muhammad Yusri Bachtiar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The core component of gross motor skills is the ability to use the large muscles in the body to perform physical movements that involve coordination and strength. This research aims to determine the effect of audio-visual based learning media on gross motor skills in children in kindergarten. This research uses a quantitative experimental approach with a pretest-posttest nonequivalent control group design. The sample was taken using a saturated sampling technique, consisting of 20 children: 10 in the control class and 10 in the experimental class. Data was collected through observation, interviews and documentation. The results showed that the experimental class that used audio-visual learning media had a higher increase in gross motor skills than the control class. Based on the Wilcoxon test, there is a significant influence of audio-visual based learning media on gross motor skills in kindergarten children aged 5-6 years in group B2 at Al-Biruni Mandiri Jipang Kindergarten.